PENGKAJIAN USAHATANI PADI GOGO DI KABUPATEN PANDEGLANG - Purba, Resmayeti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
Development of upland rice is one of the answers in increasing rice production, but the productivity of upland rice in Banten is still very low. One reason is the low use of improved varieties. But of the many upland rice varieties are not all suitable to be developed in a region. To find suitable varieties are developed in a region need to be an assessment of the introduction of varieties to obtain location-specific adaptive varieties. Assessments conducted in Cisehreheun Village, Cigeulis Sub district, Pandeglang District, during June-September 2013. Assessments using a randomized block design with upland rice varieties as treatment used are Inpago-4, Inpago- 5, Inpago- 6, Situbagendit, Stone Tegi and local varieties as a comparison, each variety was repeated 4 times. To determine the feasibility of technology to analyze revenue and cost (B/C), while for measuring the level of technological excellence applied to farmers to use marginal benefit cost ratio analysis (MBCR). The results showed that varieties Inpago 5 generate the highest production (3.5 t/ha). The results of financial analysis shows Inpago-5 provide the highest profits with a gross value of B/C 2.18 and the marginal value of B / C of 4.69.. Based on the results of the study, varieties Inpago-5 is a decent variety of adaptive and developed by farmers.